Design of a Portable Tidal Power Plant (PLTPS) Using Static Feet - Abror, Rahmatul; Wicaksono, Indro; Izzuddin, Ahmad (Universitas Panca Marga, 2022)
The potential of marine energy to generate electricity is one of the potentials that is not widely known to the general public. One of the natural phenomena that can be used as a power plant is the tides of sea water. Tidal Power Plant is a power plant using sea water when it is high tide and using estuary water power when the sea water is receding. Tidal Power Plants are generally built permanently using dams, then a Portable Tidal Power Plant is developed that can be placed on the beach when the tide is high and in the estuary when the sea water is receding. The method used in this research is the experiment method on Portable Tidal Power Plant. The Portable Tidal Power Plant uses seawater and estuary water to turn the mill, then the windmill will produce mechanical energy, and the generator will convert the mechanical energy from the wheel into electrical energy. The Portable Tidal Power Plant was tested on the beach when the sea water is high, the highest voltage is 3.3 V and the highest RPM is 413 RPM. When tested on the estuary when the sea water is receding, the highest voltage is 2.6 V and the highest RPM is 284.4 RPM